Implementasi Akad Bai' Bitsaman Ajil (BBA) pada Platform E- Commerce Shopeepay Later - Mufidatul Himmah; Tutut Maptuhatul Hairiyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to investigate the implementation of the Bai' Bitsaman Ajil (BBA) Agreement in the context of e-commerce. The BBA Agreement is a sales contract with deferred payment, where the buyer and seller agree that payment is made in installments over a certain period of time. ShopeePay Later is one of the popular payment options in e-commerce, which allows users to purchase products with deferred payment or installments. This study analyzes how the principles of BBA are integrated into the Shopeepay Later system, and identifies the challenges and opportunities that arise from the implementation of this agreement on the e-commerce platform. This implementation is also expected to increase Islamic financial inclusion in e-commerce, providing a more suitable financing alternative for Muslim consumers. However, there are challenges in its implementation, such as adjusting the technology system and the need for education for users regarding the concept and benefits of BBA. This study concludes that with proper regulation and compliance with the terms of the agreement, BBA can be implemented in ShopeePay Later to support fair and sharia-compliant transactions, as well as increase Islamic financial inclusion in the e-commerce ecosystem.